Student and virtual learning environment interaction. Research of advanced attitudes - Tankelevičienė, Lina (Lietuvos matematikos rinkinys, 2001)
Educational institutions are interested in attempting to increase the variety and number of course offerings by using alternative delivery systems including the Intemet. Implementing virtual learning environments is one of the ways to do so. This paper deals with results of questionnaire, which was made to identify advanced students and schoolchildren attitudes towards virtual learning environments.